Corroles at the Real Solid–Liquid Interface: In Situ STM Investigation of a Water‐Soluble Corrole Layer Deposited onto Au(111). Issue 66 (2nd November 2018) - Bonanni, Beatrice; Fazi, Laura; Fanfoni, Massimo; Sgarlata, Anna; Caroleo, Fabrizio; Pomarico, Giuseppe; Galloni, Pierluca; Sabuzi, Federica; Persichetti, Luca; Paolesse, Roberto; Goletti, Claudio
Abstract: Corrole derivatives have been recently employed in many applications at the solid–liquid interface. Therefore, the structural arrangement of the molecular layers in direct contact with the liquid is of fundamental interest. We investigated in solution the deposition of molecular layers of the previously prepared water‐soluble phosphorus complex of a 2‐sulfonato‐10‐(4‐sulfonatophenyl)‐5, 15‐dimesitylcorrole [see synthesis in our previous paper, M. Naitana et al., Chem. Eur. J .2017, 23, 905–916]. The layer formation of P corroles onto the Au(111) surface was monitored by STM in situ, that is, with the substrate immersed in the solution. Marked differences in the morphology between the organic layer formed on the substrate and that deposited after solvent evaporation (drop casting) are reported. In particular, the coating of gold was more effective and stable in the presence of liquid. Preservation of functionality of the corrole molecules after adsorption was verified. This result validates the relevance of corrole layers at the solid–liquid interface to exploit the peculiar properties of these molecules in real‐world applications. Abstract : Monitoring of layer formation of a phosphorus corrole onto the Au(111) surface was performed by STM in situ, that is, with the substrate immersed in the solution. Preservation of the functionality of corrole molecules after adsorption was verified.